KORELASI PENGUASAAN MUFRODAT BAHASA ARAB UNTUK MENINGKATKAN HASIL BELAJAR BAHASA ARAB DI PONDOK PESANTREN MODERN MUHAMMADIYAH PACIRAN LAMONGAN - Maftuhah; Indah Nur Farizah (STIT Muhammadiyah Paciran Lamongan, 2025)
The purpose of this study was to determine the learning outcomes of students in Arabic language subjects in class VII through mastery of Arabic Mufrodat at the Modern Islamic Boarding School of Muhammadiyah Paciran, the purpose of this study was to determine the learning outcomes of students in Arabic language subjects, and to determine whether there was a significant effect on the mastery of Arabic Mufrodat in the learning outcomes of students in Arabic language subjects. This research was conducted at the Modern Islamic Boarding School Muhammadiyah Paciran in the 2024/2025 academic year. This type of research uses a quantitative approach with a total of 26 respondents, using sample data. Data collection using pre-test and post-test questions. Based on the results of hypothesis testing using a significant test (t-test) obtained t_ (count) of 8.0719, then compared with t_ (table) for a significance level of 5% (0.05) using a two-party test dk = n-2 = 24 then obtained t_ (table) of 2.0638. With this, it is known that t_(calculated) (8.0719) > t_(table) (2.0638), then H_o is rejected and H_a is accepted. It can be concluded that the mastery of Arabic Mufrodat has an influence on the learning outcomes of Arabic class VII at the Modern Islamic Boarding School Muhammadiyah Paciran in the 2024/2025 academic year.